Probing Islamic Values of Business Principles and Ethics - Nur, Iffatin; Asiyah, Binti; Puspitarini, Reni; Umam, Syamsul (International Journal of Scientific Research and Management (IJSRM), 2019)
In Islam, business is one of the most important parts of mu’āmalah (worldly transaction) and gets a very serious attention. Islam teaches the values that must be obeyed and followed by its adherents when conducting business. Unfortunately, the present reality shows that there are still many Muslims who prefer opting and practicing business principles and methods that may not contain and display Islamic values in their practices. This paper is aimed to explore what values are taught by Islam in conducting a good and permissible business, principally and ethically. The study was a library research employing the discourse analysis. The results of this study show that Islam teaches a very comprehensive concept of business pertaining to its principles and ethics. They also show that, contrary to conventional business principles, Islamic ones accentuate the aspect of divinity in business. This is so because basic principles and ethics taught by Islam through its maqāṣid sharī'ah in conducting mu’āmalah, in this case doing business, are meant none other than to bring benefits to mankind justly and proportionally as well as resisting any harm from them.